Environmental Life-Cycle Analysis as a Tool for Sustainability Studies: A Complete Learning Experience - Venkatesh, G (Problemy Ekorozwoju, 2019)
This article first presents Environmental Life-Cycle Analysis (E-LCA) as a complete learning experience for university students of environmental science/engineering, enabling the acquisition of the four levels of knowledge, of the Structure of the Observed Learning Outcome (SOLO) taxonomy. The four steps of an E-LCA, interestingly, mirror the hierarchy of knowledge-levels defined by the SOLO taxonomy. In the light of the fact that it is generally difficult to accomplish this ascent from declarative knowledge to functional knowledge, in a systematic manner, in many university courses, the complete learning experience guaranteed by E-LCA must stand out conspicuously.